Impact of host plants, slope position and subsidence on arbuscular mycorrhizal fungal communities in the coal mining area of north-central China. (April 2019) - Bi, Yinli; Xie, Linlin; Wang, Jin; Zhang, Yanxu; Wang, Kun
Abstract: Coal mining results in surface subsidence and make ecological environment more fragile. The dynamics of arbuscular mycorrhizal (AM) fungi response to host plants, slope position and subsidence have been investigated at the Shendong Bulianta coal mining area in north-central China. A total of 57 AM fungal operational taxonomic units (OTUs) were identified and subdivided into five genera. It was noticed that at the top slope position, the AM fungal infection and extraradical hyphal (ERH) density were significantly higher than at the middle and bottom, AM fungal diversity indices showed a significant decrease with the increasing slope position. Significantly different phylogenetic indices were observed among the three host plants. In addition, the AM fungal ERH density and phylogenetic index were observed to be significantly higher in areas without subsidence. Soil available P and pH significantly influenced AM fungal infection and ERH density. The findings highlight that host plants, slope position and subsidence has strong influence on AM fungal community via edaphic variables change. This study provided the groundwork to further clarify AM fungal ecological function, which can potentially help in vegetation restoration and reduced erosion in coal mining areas. Highlights: The examined plants are endemic mid-arid species in quicksand environments, which can reduce desertification. Arbuscular mycorrhizal (AM) fungal communities are useful indicators for evaluating soil quality of coal mining area. Dynamics of AM fungi are influenced by plants species, slope and subsidence.